Libraries for a time of crisis. Building and staff - Fuentes Romero, Juan José (Revista General de Información y Documentación, 2012)
From a definition of “crisis”, and using a systemic methodology, here appears questions as books, publishing and bookshops. The core of this article is about the library in itself considered, as well as building, equipment and staff. In the conclusions it is signed up how crisis is a threat, obviously, but as well it represents opportunities.
Keywords: Libraries; Economical Crisis; Crisis in books; publishing and bookshops; Library buildings; Staff library.